Infometrics and Music Information Retrieval: An Infometric Examination of a Folksong Database - Downie, Stephen J. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This study examined the informetric properties of intervallic n-grams as derived from a database of 9354 folksongs. The informetric properties of the melodies were compared and contrasted to those of traditional text. Understanding these similarities/dissimilarities can play a vital role in the creation of a successful Music Information Retrieval (MIR) system.